Thyroidopathy and Age-Related Macular Degeneration: Is There Any Correlation - Chatziralli, Irini (Biomed Hub, 2017)
PURPOSE: The purpose of this study was to evaluate whether inherent sociodemographic parameters, lifestyle features, as well as medical data may be potential risk factors for the presence of age-related macular degeneration (AMD). METHODS: Participants in our study were 114 patients with AMD, 63 males and 51 females, and 100 control subjects without any ocular disease. Demographic data, lifestyle data, medical history, and comorbidities were recorded and analyzed as potential risk factors for the presence of AMD. RESULTS: There was no statistically significant difference between patients and controls regarding age, gender, smoking, alcohol consumption, walking, exercise, presence of hypertension, diabetes mellitus, myoskeletal problems, migraine, and cancer. Marital status, higher educational level, cardiovascular disorders, and thyroidopathy were found to be significantly associated with AMD. CONCLUSIONS: Apart from already reported risk factors for AMD, thyroidopathy was associated with AMD.